1983
DOI: 10.1111/j.1365-2621.1983.tb00292.x
|View full text |Cite
|
Sign up to set email alerts
|

Thin‐layer air drying of soybeans and white beans

Abstract: A thin-layer air drying apparatus was designed and constructed to determine the drying characteristics of various agricultural and food products. The equipment was designed to monitor the weight loss during drying and to operate over a practical range of air temperatures and humidities. This paper presents a description of the apparatus and an evaluation of its performance.The results of studies conducted to determine the thin-layer drying behaviour of soybeans and white beans are included.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
11
0

Year Published

1988
1988
2008
2008

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 57 publications
(15 citation statements)
references
References 9 publications
3
11
0
Order By: Relevance
“…The experimental results were showed that air temperature is considered as the most important factor affected drying rate. Different authors reported similar results on drying of vegetables (Hatamipour & Mowla, 2003;Hutchinson & Otten, 1983).…”
Section: Drying Curvessupporting
confidence: 76%
See 2 more Smart Citations
“…The experimental results were showed that air temperature is considered as the most important factor affected drying rate. Different authors reported similar results on drying of vegetables (Hatamipour & Mowla, 2003;Hutchinson & Otten, 1983).…”
Section: Drying Curvessupporting
confidence: 76%
“…This model was also used to fit the experimental data of soybean, white bean, green bean and corn (Doymaz & Pala, 2003;Hutchinson & Otten, 1983;Yaldiz & Ertekin, 2001). The model is given as…”
Section: Mathematical Modellingmentioning
confidence: 99%
See 1 more Smart Citation
“…Two-term exponential model is the first two terms of general series solution to the analytical solution of FickÕs second law, and has also been used to describe drying agricultural products (Hutchinson & Otten, 1983).…”
Section: Mathematical Modellingmentioning
confidence: 99%
“…Drying techniques were drawn attention of many researchers and many studies were done on the world (Hutchinson and Otten, 1983;Kitic and Viollaz, 1984). The most important point to pay attention is to remove wax film on grape that resists mass transfer during drying.…”
Section: Introductionmentioning
confidence: 99%